Phosphine inhalation, case series of domestic unintentional poisoning commonly used as anti-bed bug chemical from a low income country - Afzal, Badar; Siddiqui, Emaduddin; Kazi, Ghazala Irfan; Khan, Irum Qamar; Daniyal, Muhammad; Khan, Muhammad Abdul Raffay (International Journal Of Community Medicine And Public Health, 2018)
Phosphine poisoning is an uncommon but hazardous public health issue. It is widely used chemical compound as insecticides domestically and exposure to this chemical is mostly accidental especially in children, which may lead to fatal symptoms if not managed immediately. Previous studies have explored the mechanism of its deleterious effect. However, literature on presentation of phosphine poisoning is sparse. Medical records, from January 2005 to September 2013, with patients presenting to ED of Aga Khan University Hospital were reviewed after successfully taking ERC approval from the hospital. Patients with confirm phosphine poisoning were identified and further details were noted from their medical records. We identified seven cases of phosphine poisoning during the study period. Majority patients presented with generalized weakness, diarrhea, vomiting and drowsiness after exposure to phosphine containing insecticides, mostly exposed within past two days of symptoms and presentation. Six out of seven patients were successfully managed and discharged while one of the patient couldn’t be saved. The objective of this study was to investigate various presentations of phosphine poisoning to Emergency Department (ED) in a low-income setting in Karachi, Pakistan and bring it to attention of the need to replace insecticides with a safer chemical compound and keep children out of reach from such toxins. Moreover increase awareness program and proper labeling and precautions should be written on all commonly sold pesticides and the constituent of hazardous compounds they contain.